Natural products targeting AMPK signaling pathway therapy, diabetes mellitus and its complications - Li, Min; Ding, Lu; Cao, Liyuan; Zhang, Zepeng; Li, Xueyan; Li, Zirui; Xia, Qinjing; Yin, Kai; Song, Siyu; Wang, Zihan; Du, Haijian; Zhao, Daqing; et al. (Frontiers in Pharmacology, 2025)
Diabetes mellitus (DM) ranks among the most prevalent chronic metabolic diseases, characterized primarily by a persistent elevation in blood glucose levels. This condition typically stems from either insufficient insulin secretion or a functional defect in the insulin itself. Clinically, diabetes is primarily classified into type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM), with T2DM comprising nearly 90% of all diagnosed cases. Notably, the global incidence of T2DM has surged dramatically over recent decades. The adenylate-activated protein kinase (AMPK) signaling pathway is crucial in regulating cellular energy metabolism, marking it as a significant therapeutic target for diabetes and related complications. Natural products, characterized by their diverse origins, multifaceted bioactivities, and relative safety, hold considerable promise in modulating the AMPK pathway. This review article explores the advances in research on natural products that target the AMPK signaling pathway, aiming to inform the development of innovative antidiabetic therapies.